The wisdom of Sally Red Shoes : a novel - Hogan, Ruth, 1961- (Crooked Lane Books, 2019)
"They say friends make life worth living... Once a spirited, independent woman with a rebellious streak, Masha's life was forever changed by a tragic event twelve years ago. Unable to let go of her grief, she finds comfort in her faithful canine companion Haizum, and peace in the quiet lanes of her town's swimming pool. Almost without her realizing it, her life has shuddered to a halt. It's only when Masha begins an unlikely friendship with the mysterious Sally Red Shoes, a bag lady with a prodigious voice and a penchant for saying just what she means, that a new world of possibilities opens up: new friendships, new opportunities, and even a chance for new love. For the first time in years, Masha has the chance to start living again. But just as Masha dares to imagine the future, her past comes roaring back... Like her beloved debut, The Keeper of Lost Things, Ruth Hogan's second novel introduces a cast of wonderful characters, both ordinary and charmingly eccentric, who lead us through a moving exploration of the simple human connections that unite us all."--provided by Amazon.com.